MODELING THE METHODOLOGICAL ACTIVITIES OF TEACHERS OF TECHNOLOGY EDUCATION - Dang Minh K (International Journal of Literature and Language Studies, 2022)
This article presents ideas on the modeling of the methodological activities of teachers of technology education and their current state. Educating the younger generation requires great responsibility and knowledge from educators. The methodological activities of the teacher are of great importance in the development of science.